TO THE JUBILEE OF PROFESSOR STEPANOVA ELEONORA FEDOROVNA - D. V. Kompantsev; V. M. Kishchenko; D. V. Veselova; K. N. Koryanova (Фармация и фармакология (Пятигорск))
The article is devoted to the anniversary of Professor Eleonora Fedorovna Stepanova – a bright representative of the Russian intelligentsia: a talented lecturer, an inventor, an author of numerous books, an internationally recognized scholar!